Mass notification and crisis communications : planning, preparedness, and systems - Walker, Denise C. (CRC Press, 2012)
Mass communication in the midst of a crisis must be done in a targeted and timely manner to mitigate the impact and ultimately save lives. Based on sound research, real-world case studies, and the author's own experiences, Mass Notification and Crisis Communications: Planning, Preparedness, and Systems helps emergency planning professionals create a crisis communications plan that works by establishing upfront relationships with responders, enacting protocols, and utilizing technology to effectively message the intended audience. Providing communication best practices to professionals, the boo.